Photocatalytically Decorated Au-nanoclusters TiO2 Nanofibres for Elemental Mercury Vapor Detection. (2015) - Macagnano, A.; Zampetti, E.; Perri, V.; Bearzotti, A.; Sprovieri, F.; Pirrone, N.; Esposito, G.; De Cesare, F.
Abstract: Electrospun nanofibrous nets of titania (anatase) were deposited on interdigitated microelectrodes and photocatalytically decorated with gold nanoclusters (AuNCs) upon UV irradiation. The resulting devices appeared to be conductive even at room temperature (Ohmic behavior), and were investigated as potential chemosensors capable of entrapping and detecting elemental mercury vapors in the atmosphere. The strong affinity and specificity of Au for Hg 0 conferred to AuNCs a key role in mercury sensing, by inducing a decrease in current upon mercury adsorption. Sensors conductivity appeared not to be dependent on humidity. The resulting chemosensors are expected to be inexpensive, very stable (due to the peculiar structure), and requiring low power, low maintenance and simple equipment to work.